Molecular Surveillance of HIV-1 Infection in Krasnoyarsk Region, Russia: Epidemiology, Phylodynamics and Phylogeography - Neshumaev, Dmitry; Lebedev, Aleksey; Malysheva, Marina; Boyko, Anatoly; Skudarnov, Sergey; Ozhmegova, Ekaterina; Antonova, Anastasia; Kazennova, Elena; Bobkova, Marina (Current HIV Research, 2019)
Background: The information about the dynamics of the viral population and migration events that affect the epidemic in different parts of the Russia is insufficient. Possibly, the huge size of the country and limited transport accessibility to certain territories may determine unique traits of the HIV-1 evolutionary history in different regions. Objective: The aim of this study was to explore the genetic diversity of HIV-1 in the Krasnoyarsk region and reconstruct spatial-temporal dynamics of the infection in the region. Methods: The demographic and virologic data from 281 HIV-infected individuals in Krasnoyarsk region collected during 2011-2016 were analyzed. The time to the most recent common ancestor, evolutionary rates, population growth, and ancestral geographic movements was estimated using Bayesian coalescent-based methods. Results: The study revealed moderate diversity of the HIV-1 subtypes found in the region, which included A6 (92.3%), CRF063_02A (4.3%), B (1.1%), and unique recombinants (2.5%). Phylogenetic reconstruction revealed that the A6 subtype was introduced into Krasnoyarsk region by one viral lineage, which arose around 1996.9 (1994.5-1999.5). The phylogeography analysis pointed to Krasnoyarsk city as the geographical center of the epidemic, which further spread to central neighboring districts of the region. At least two epidemic growth phases of subtype A6 were identified which included exponential growth in early-2000s followed by the decline in the mid/late 2010s. Conclusion: This study demonstrates a change in the genetic diversity of HIV-1 in the Krasnoyarsk region. At the beginning of the epidemic, subtype A6 prevailed, subtypes B and CRF063_02A appeared in the region later.
Keywords: Bayesian analysis